Heterogeneity in subjective wellbeing : an application to occupational allocation in Africa (2013)
By exploiting recent advances in mixed (stochastic parameter) ordered probit estimators and a unique longitudinal dataset from Ghana, this paper examines the distribution of subjective wellbeing across sectors of employment. We find little evidence for the overall inferiority of the small firm informal sector relative to the formal salaried sector at the conditional mean. Moreover, the estimated underlying random parameter distributions unveil substantial latent heterogeneity in subjective wellbeing around the central tendency that fixed parameter models cannot detect. All job categories contain substantial shares of both relatively happy and disgruntled workers.